Seasonal Bacterial Production in a Dimictic Lake as Measured by Increases in Cell Numbers and Thymidine Incorporation - Lovell, Charles R. (1985)
Rates of primary and bacterial production in Little Crooked Lake were calculated from the rates of incorporation of H(14)CO(3)(−) and [methyl-(3)H]thymidine, respectively. Growth rates of bacteria in diluted natural samples were determined for epilimnetic and metalimnetic bacterial populations during the summers of 1982 and 1983. Exponential growth was observed in these diluted samples, with increases in cell numbers of 30 to 250%. No lag was observed in bacterial growth in 14 of 16 experiments. Correlation of bacterial growth rates to corresponding rates of thymidine incorporation by natural samples produced a conversion factor of 2.2 × 10(18) cells produced per mole of thymidine incorporated. The mass of the average bacterial cell in the lake was 1.40 × 10(−14) ± 0.05 × 10(−14) g of C cell(−1). Doubling times of natural bacteria calculated from thymidine incorporation rates and in situ cell numbers ranged from 0.35 to 12.00 days (median, 1.50 days). Bacterial production amounted to 66.7 g of C m(−2) from April through September, accounting for 29.4% of total (primary plus bacterial) production during this period. The vertical and seasonal distribution of bacterial production in Little Crooked Lake was strongly influenced by the distribution of primary production. From April through September 1983, the depth of maximum bacterial production rates in the water column was related to the depth of high rates of primary production. On a seasonal basis, primary production increased steadily from May through September, and bacterial production increased from May through August and then decreased in September.